Pengaruh Gaya Kepemimpinan, Disiplin, dan Motivasi Kerja Terhadap Kinerja Karyawan pada PD Intan Bestari Kabupaten Garut - Pani Febrianti; Isnurrini Hidayat Susilowati (LPPM Universitas Bina Sarana Informatika, 2023)
This study aims to determine the effect of leadership style, work discipline, and work motivation on the performance of employees of PD Intan Bestari Kabupaten Garut. Achieving performance by organizational standards and expectations is very important, as is setting vision and goals. However, various elements, including culture, leadership, salary, motivation, workplace environment, and organizational commitment, have an impact on personnel. All of these elements are critical in inspiring workers to produce the desired results. The research method used is a survey approach, using quantitative data, namely primary data obtained through questionnaires. The population in this study were employees of PD Intan Bestari Kabupaten Garut with a sample of 30 employees. Data testing uses multiple linear regression statistical analysis methods, T-test, and F-test with SPSS V25.0 software. The results showed that simultaneously leadership style, work discipline, and work motivation affect employee performance. Likewise, the results of the t-test show that leadership style, work discipline, and work motivation each affect employee performance. So, it can be concluded both partially and simultaneously that leadership style, work discipline, and work motivation affect employee performance at PD. Intan Bestari Kabupaten Garut.